PENILAIAN PRESTASI KERJA MENGGUNAKAN APLIKASI ONLINE PADA PEGAWAI NEGERI SIPIL - Agus Iwan Mulyanto; Erialdy Erialdy; Sugeng Lubar Prastowo; Ade Indra Permana (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
The appraisal of civil servants achievement is an effort made by government institution to guarantee the objectivity staff performance development in their environment. The government of South Tangerang City in 2018 issued Mayor Regulation No. 5 regarding the Provision of Additional Income for Civil Servants and Prospective Civil Servants in the Government of the City of South Tangerang which also includes achievement appraisals using an online-based application known as APIK. This study focuses on the implementation of the performance appraisal policy of Civil Servants in the Regional Government of South Tangerang City based on the APIK online application. The research method used is a descriptive qualitative, the research subjects are The Agency for Personnel Education and Training of South Tangerang, Public Health Office of South Tangerang and five civil servants. Data collection technique used are interview and voice recording. The analysis of data research uses 4 steps ie. data collection, data reduction, data presentation and conclusion drawing or verification. Data validation testing used is source triangulation techniques. The results of this study indicate that the implementation of working achievement appraisal using online-based applications, is an innovation in the work of performance appraisal effort and also shows that the Government of South Tangerang City in the of assessing work achievement to Civil Servants in the region   has adapted to the development of digital technology that currently exists.